2006
DOI: 10.1001/archneur.63.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of the Parkin Gene in Early-Onset Parkinson Disease

Abstract: Background: Mutations in parkin are estimated to account for as much as 50% of familial Parkinson disease (PD) and 18% of sporadic PD. Single heterozygous mutations in parkin in both familial and sporadic cases may also increase susceptibility to PD. To our knowledge, all previous studies have been restricted to PD cases; this is the first study to systematically screen the parkin coding regions and exon deletions and duplications in controls.Objective: To determine the frequency and spectrum of parkin variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 40 publications
4
65
0
Order By: Relevance
“…Overall, PINK1 heterozygotes were more frequent among cases than in controls (1.7% vs. 1.0%), with an OR of 1.62 (95%CI 0.88 -2.99) that did not reach statistical significance (p=0.121). We applied the same meta-analysis to published Parkin case-control screenings (Lincoln et al, 2003;Clark et al, 2006;Kay et al, 2007;Klein et al, 2007;Lesage et al, 2007), obtaining frequencies more than doubled in cases than in controls (4.5% vs. 1.8%) and a significant OR of 2.53 (95%CI 1. 40-4.56, p=0.002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, PINK1 heterozygotes were more frequent among cases than in controls (1.7% vs. 1.0%), with an OR of 1.62 (95%CI 0.88 -2.99) that did not reach statistical significance (p=0.121). We applied the same meta-analysis to published Parkin case-control screenings (Lincoln et al, 2003;Clark et al, 2006;Kay et al, 2007;Klein et al, 2007;Lesage et al, 2007), obtaining frequencies more than doubled in cases than in controls (4.5% vs. 1.8%) and a significant OR of 2.53 (95%CI 1. 40-4.56, p=0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Diagram of odds ratios (ORs, diamonds) and 95% confidence intervals (CI, vertical bars) calculated for heterozygous rare variants in the PINK1 and Parkin genes from selected mutation screenings of cases and controls (see Methods). In the studies by Clark et al (2006) and Lesage et al (2007), ORs cannot be calculated thus the reported figures represent the frequency of heterozygous patients (CI in brackets). …”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14]16,17 However, not all studies found a higher frequency in patients than in controls. 20 Although the sampling of patients varied across studies (early-onset, late-onset, familial PD), the frequency of PARK2 mutations in our patients with PD, when subgrouped to match each study, are generally in line with most prior studies.…”
Section: Figure 3 Moving Average Plots Of Park2 Mutation Frequency Asmentioning
confidence: 96%
“…The majority of positive results are heterozygous and difficult for clinicians to interpret because whether having one mutation can cause, increase risk, or accelerate onset of Parkinson disease (PD) is unknown. [9][10][11][12][13][14][15][16][17][18][19][20][21] The second aim of our study was to determine, conclusively, if heterozygous mutations are associated with PD. We designed this study specifically to address this question, and to that end, amassed a large sample size to ensure analytic power, analyzed the coding regions for all types of variations, and importantly, used the same rigorous mutation analysis and validation methods in control subjects as in patients.…”
mentioning
confidence: 99%
“…Many mutations are homozygous or compound heterozygous, but there also exist cases with one single Parkin mutation [222,225], although it is controversial whether these are disease-causing mutations or merely polymorphisms [226].…”
Section: Genes Associated With Autosomal Recessive Pdmentioning
confidence: 99%